Mycobacterial PPE13 activates inflammasome by interacting with the NATCH and LRR domains of NLRP3. Issue 9 (1st August 2020) - Yang, Yang; Xu, Pianpian; He, Ping; Shi, Fushan; Tang, Yiran; Guan, Chiyu; Zeng, Huan; Zhou, Yingshan; Song, Quanjiang; Zhou, Bin; Jiang, Sheng; Shao, Chunyan; et al.
Abstract: Pathogenic mycobacteria, such as Mycobacterium tuberculosis, Mycobacterium bovis, and Mycobacterium marinum, can trigger NLRP3 inflammasome activation leading to maturation and secretion of interleukin 1β (IL‐1β). However, the mycobacterial factors involved in the activation of NLRP3 inflammasome are not fully understood. Here, we identified that the PPE family protein PPE13 was responsible for the induction of IL‐1β secretion in a NLRP3 inflammasome‐dependent manner. We found that the recombinant Mycobacterium smegmatis expressing PPE13 activates NLRP3 inflammasome, thereby inducing caspase‐1 cleavage and IL‐1β secretion in J774A.1, BMDMs, and THP‐1 macrophages. To examine whether this inflammasome activation was triggered by PPE13 rather than components of M. smegmatis, PPE13 was introduced into the aforementioned macrophages by lentivirus as a delivery vector. Similarly, this led to the activation of NLRP3 inflammasome, indicating that PPE13 is a direct activator of NLRP3 cascade. We further demonstrated that the NLRP3 complex activated the inflammasome cascade, and the assembly of this complex was facilitated by PPE13 through interacting with the LRR and NATCH domains of NLRP3. Finally, we found that all PPE13 proteins isolated from M. tuberculosis, M. bovis, and M. marinum can activate NLRP3 inflammasome through binding to NLRP3, which requires C‐terminal repetitive MPTR domain of PPE13. Thus, we, for the first time, revealed that PPE13 triggers the inflammasome‐response by interacting with the MPTR domain of PPE13 and the LRR and NATCH domains of NLRP3. These findings provide a novel perspective on the function of PPE proteins in the immune system during mycobacteria invasion.